Para‐Selective Cyanation of Arenes by H‐Bonded Template. Issue 50 (11th August 2020) - Pimparkar, Sandeep; Bhattacharya, Trisha; Maji, Arun; Saha, Argha; Jayarajan, Ramasamy; Dutta, Uttam; Lu, Gang; Lupton, David W.; Maiti, Debabrata
Abstract: The significance of site selective functionalization stands upon the superior selectivity, easy synthesis and diverse product utility. In this work, we demonstrate the para ‐selective introduction of versatile nitrile moiety, enabled by a detachable and reusable H‐bonded auxiliary. The methodology holds its efficiency irrespective of substrate electronic bias. The conspicuous shift in the step energetics was probed by both experimental and computational mechanistic tools, which heralds the inception of para ‐deuteration. The synthetic impact of the methodology was highlighted with reusability of directing group and post synthetic modifications. Abstract : Para ‐Selective Cyanation of Arenes : Site selectivity for distal para C−H bond of arene has always remain an important challenge since its solicits a gigantic (16–17‐membered) metalacyclic intermediate compared to proximal ortho or even distal meta ‐. A comprehensive experimental and computational study on distal para ‐C−H cyanation concreted a new way to introduce the versatile nitrile moiety selectively using a detachable directing group. Iterative multi‐functional decoration of arenes makes this method more appealing. The notable shift in the step energetics was probed by both experimental and computational mechanistic tools, which heralds the inception of para ‐deuteration.